Gender differences in young adults’ inclination to sacrifice career opportunities in the future for family reasons: comparative study with university students from Nairobi, Madrid, and Reykjavik - Fernández-Cornejo, José A; Escot, Lorenzo; Kabubo-Mariara, Jane; Kinuthia, Bethuel K; Eydal, Guðný Björk; Bjarnason, Tómas (University of Nairobi, 2015)
This article addresses the question of to what extent young people show an inclination to accept some sacrifice in their career progression in the future in order to reach a better work–family balance. Data come from a survey conducted among a sample of 2383 university students who attended three universities: University of Nairobi, University of Iceland, and Complutense University of Madrid. After building a set of indicators about career and family involvement aspirations of respondents, and after conducting a statistical and regression analysis, this research shows that young women (on average) still have a greater predisposition than young men to make sacrifices in the future in their working careers in order to achieve a better work–family balance. Moreover, having a high degree of leadership aspirations and belonging to an egalitarian household tend to reduce the inclination to sacrifice career opportunities, whereas having a high inclination to be involved in childcare in the future and having the perception of a future work–family conflict tend to increase it. Gender attitudes have a differential effect on female and male students: having traditional gender attitudes tends to increase the inclination to sacrifice career opportunities in the case of female students and reduce it in the case of male students.